Faktor-Faktor Yang Mempengaruhi Profitabilitas Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Alfi Yulianto; Aditya Hermawan (Program Studi Akuntansi PSDKU Universitas Pattimura, 2021)
The purpose of this study was to identify and analyze the factors that affect the profitability of manufacturing companies listed on the Indonesia Stock Exchange. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange. The choice of a manufacturing company because this company has a high profitability ratio (ROA), this means that the company in obtaining high profitability is influenced by many factors. While the selection of the period 2017 - 2019 as a sample because it can describe the relatively new conditions in the Indonesian capital market. The sampling technique used is the purposive sampling method, the type of judgment sampling, namely the sample is selected using certain considerations that are tailored to the research objectives or research problems developed. The source of data used in this study is secondary data derived from the sample company's financial statements obtained from the Indonesia Stock Exchange through its official website, namely www.idx.co.id and previous research reports that support this research. the current ratio hypothesis is not accepted, which means that the current ratio has no effect on return on assets. This is because a current ratio that is too high indicates an excess of idle current assets, so it is not good for the company's profitability because current assets generate lower returns than fixed assets. Debt to total asset ratio is not accepted, which means debt to total asset ratio has no effect on return on assets. This is due to the small portion of the debt to total asset ratio, causing a small amount of loan capital used to generate profitability for the company. Sales growth is not accepted, which means that sales growth has no effect on return on assets. This is due to the lack of increasing sales growth from year to year, causing the company's profitability to be low.